(untitled) (Innovative professional education, 2025)
Integrative processes are aimed at building the educational process in such a way that knowledge is interconnected, complementary and acquires new meaningful shades. This approach helps to broaden students’ horizons, deepen their knowledge and adapt to new fields of study. Adopting the Polish experience of integrative teaching and adapting it to the Ukrainian education system can significantly improve teaching methods. The use of complex knowledge, the establishment of interdisciplinary links and the combination of different teaching approaches become the basis for a creative and effective educational process in pre- and post-secondary institutions